INNOVATIVE BIOCHEMICAL MARKERS OF PRODUCTIVITY IN WOMEN WITH PREMATURE OVARIAN FAILURE - Karimova, N.N.; Naimova, N.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
In accordance with the purpose and objectives of this study, we studied patients with premature ovarian insufficiency. As mentioned above, the patients of the main group (n=112) were divided into two groups: the first group (n=59) included patients with a STUMP who underwent surgery with a decrease in ovarian reserve; the second group (n=53) included patients with a STUMP, without surgery, but with a decrease in ovarian reserve. The conducted studies showed that in women with PCOS of the 1st group with surgical interventions, the FSH content was 1.7 times higher than the values of the control group, In patients of the 2nd group we also observed an increase in the level of FSH by 1.58 times relative to the values of the control group. In addition, we collected 30 practically healthy women in the control group.